In chains, yet prophetic! An African liberationist reading of the portrait of Paul in Acts 27 - Mtshiselwa, Ndikho (HTS teologiese studies, 2015)
New Testament scholars have argued that Luke-Acts presents an apologetic historiography and political propaganda which portrayed Roman officials as saviours of the world. The problem with the discourse on the apologetic historiography and political propaganda in Luke-Acts is that the presence of various forms of oppression behind and in the text becomes hidden. Thus, it is pertinent to highlight the reality of oppression as well as the prophetic voice that responded to them, as illustrated by the text of Acts 27. In this article, Lucky Dube’s Mickey Mouse freedom song is employed as a hermeneutical tool to unlock the meaning of Acts 27, and to argue that whereas Acts 27 contains an apologetic narrative, Paul’s prophetic voice is equally evident in the chapter. From an African liberationist perspective, lessons are therefore drawn from Acts 27 regarding the liberationist prophetic voice of Paul. In the end, this article sees Paul’s prophetic voice as an embodiment of both resilience and resistance in the face of imperialism and chains (oppression).